The Potential of Durian Seed (Durio zibethinus Murr.) as Natural Resources with Antioxidant Activity and Total Flavonoid Content - Aisyah, Siti; Harioputro, Dhani Redhono; Nurwati, Ida (Nusantara Science and Technology Proceedings, 2024)
Durian is mainly distributed in Southeast Asia and is already famous among Indonesian society. In addition, the nutritional content and unique flavor of the pulp, part of durian fruit such as the seed, peel, roots, and leaves also have many benefits. Durian seeds are known as inedible parts and should disposed of as food waste. However, these are a good source of bioactive compounds. Durian seeds contain bioactive compounds that are antioxidants, including phenolics, flavonoids, and alkaloids. Flavonoids are phenolic compounds which have good benefits for human health. This research aims to analyze the potential antioxidant activity and flavonoid content of durian seed waste. The extraction used ethanol 70%, the antioxidant activity test used a scavenging test to 2,2-diphenyl-1-pycryl-hydrazil (DPPH) radical, and total flavonoid content was determined by the UV-Vis spectrophotometry method. Based on the results, durian seed extract has antioxidant activity of 99.70 µg/ml and total flavonoid content of 23,24±0,39 mgQE/g. Durian seed extract has relatively strong antioxidant activity and contains flavonoids as a bioactive compound. This information is useful for researchers to find bioactive compounds that may be new nutraceuticals for antioxidants, anti-inflammatory, anti-diabetic, and therapeutic functional foods.